Disparitas Pemidanaan Korupsi Dalam Perspektif Kepastian Hukum dan Keadilan Publik - Erdhy Widyatama Suparno; Alwan Hadianto; Isfandir Hutasoit (JURNAL USM LAW REVIEW, 2026)
This study aims to identify patterns of sentencing disparities in corruption cases and formulate evaluative standards for assessing the legitimacy of lenient sentences from the perspective of legal certainty and public justice. The phenomenon of lenient sentences in cases involving significant state losses indicates a tension between the normative structure of sentencing and judicial practice, which has implications for declining public trust in the legal system. The urgency of this research lies in the need to conceptually explain the relationship between judicial discretion, sentencing standards, and proportionality of punishment in the eradication of corruption. This research is normative legal research with a philosophical approach used to examine the basic values of punishment and the relationship between legal certainty, justice, and the benefits of law through the perspective of Gustav Radbruch’s thinking. The results of the study show that the minimum criminal limits and sentencing guidelines have not functioned effectively as instruments for differentiating the seriousness of criminal acts, because the parameters of state losses have not been consistently integrated into sentencing standards. This study concludes that sentencing disparities reflect a structural conflict between legal certainty, judicial discretion, and demands for public justice. The novelty of this study lies in the use of Radbruch’s Formula as a normative evaluative framework for assessing the legitimacy of lenient sentences, so that sentencing disparities are understood as a manifestation of fundamental legal value conflicts, rather than merely a technical judicial issue. Penelitian ini bertujuan mengidentifikasi pola disparitas pemidanaan dalam perkara tindak pidana korupsi serta merumuskan standar evaluatif untuk menilai legitimasi vonis ringan dalam perspektif kepastian hukum dan keadilan publik. Fenomena vonis ringan pada perkara dengan kerugian negara besar menunjukkan adanya ketegangan antara struktur normatif pemidanaan dan praktik peradilan yang berimplikasi pada menurunnya kepercayaan publik terhadap sistem hukum. Urgensi penelitian terletak pada kebutuhan untuk menjelaskan secara konseptual hubungan antara diskresi hakim, standar pemidanaan, dan proporsionalitas hukuman dalam pemberantasan korupsi. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan filosofis (philosophical approach) yang digunakan untuk menelaah nilai-nilai dasar pemidanaan serta relasi antara kepastian hukum, keadilan, dan kemanfaatan hukum melalui perspektif pemikiran Gustav Radbruch. Hasil penelitian menunjukkan bahwa batas minimum pidana dan pedoman pemidanaan belum berfungsi efektif sebagai instrumen diferensiasi tingkat keseriusan tindak pidana, karena parameter kerugian negara belum terintegrasi secara konsisten dalam standar pemidanaan. Penelitian ini menyimpulkan bahwa disparitas pemidanaan mencerminkan konflik struktural antara kepastian hukum, diskresi yudisial, dan tuntutan keadilan publik. Kebaruan penelitian terletak pada penggunaan Radbruch’s Formula sebagai kerangka evaluatif normatif untuk menilai legitimasi vonis ringan, sehingga disparitas pemidanaan dipahami sebagai manifestasi konflik nilai fundamental hukum, bukan sekadar persoalan teknis peradilan.